Non-Polynomial Spline Method for a Time-Dependent Heat-Like Lane- Emden Equation - Uçar, Mehmet Fatih; Çağlar, Süleyman Hikmet (Polish Acad Sciences inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2012)
In this study, a time-dependent heat-like Lane-Emden equation is solved by using a non-polynomial spline method. An example is solved to assess the accuracy of the method. The numerical results are obtained for different values (n) of equation. The results indicate that non-polynomial spline method is effectively implemented. It is seen that results are compatible with exact solutions and consistent with other existing numerical methods.
Keywords: variational iteration method; wave-like equations; adomian decomposition method; fowler type equations; differential-equations; variable-coefficients; approximate solution; değişken yineleme yöntemi; dalga benzeri denklemler; adom ayrışma yöntemi; fowler tipi denklemler; diferansiyel denklemler; değişken katsayıları; yaklaşık çözüm